Expectations, network centrality, and public good contributions: Experimental evidence from India - Caria, A. Stefano; Fafchamps, Marcel (Journal of economic behavior & organization, 2019)
Do individuals in a position of social influence contribute more to public goods than their less connected partners? Can we motivate these influential individuals by disclosing how others expect them to act? To answer these questions, we play a public good game on a star network. The experimental design is such that efficiency and equality considerations should motivate central players to contribute more than others. Using a subject population familiar with contributions to public goods on social networks, we find that central players contribute just as much as the average of other players, leading to a large loss of efficiency. When we disclose the expectations of other players, we find that central players often adjust their contributions to meet the expectations of the group. Expectations disclosure leads to higher contributions in groups that have weak social ties outside of the experiment. In groups where ties are strong, it has no significant effect. This evidence casts doubt on the idea that individuals who, by their social position, can contribute more effectively to the public good rise to the challenge by contributing more than others. In some, but not all social groups, these individuals can be motivated to increase contributions by disclosing the expectations of others.